Pendidikan Karakter dalam Islam: Kajian Al-Qur'an dan Hadis - Firdaus Wajdi (Jurnal Studi Al-Qur'an, 2010)
This study aims at describing the definition of character education and finding the core argumentation in Islamic teaching through analysis of Quran and Hadis, the two sources in Islam. This research employs qualitative methodology and uses library research at a major method. This includes the published, online, and digital references. The output of this study shows that the character education has its argumentation in Islamic teachings, both form Quran and hadits. And it is suggested that there will be a further study to combine the values from Islamic teaching related to character education with modern method that has been developed in Western cultures.